Mature B-Cell Lymphoma and Leukemia in Children and Adolescents—Review of Standard Chemotherapy Regimen and Perspectives. (1st September 2013) - Worch, Jennifer; Rohde, Marius; Burkhardt, Birgit
<x xml:space="preserve">Abstract</x> Mature B-cell non-Hodgkin lymphoma (B-NHL) comprises more than 50% of all non-Hodgkin lymphoma (NHL) in children and adolescents. Many B-NHL subtypes frequently observed in adults are rarely diagnosed in children and adolescents. In this age group, Burkitt lymphoma (BL), Burkitt leukemia or FAB L3 leukemia (B-AL), diffuse large B-cell lymphoma (DLBCL), primary mediastinal large B-cell lymphoma (PMLBL), follicular lymphoma (FL), and aggressive mature B-NHL not further classifiable (B-NHL nfc) are the most common subtypes. Diverse clinical trials demonstrated similar results of current combination chemotherapy regimens succeeding in overall survival rates of more than 80%. However, treatment-related toxicity and the poor prognosis of relapse are serious concerns. Furthermore, specific histological B-NHL subtypes are rare in children and optimal treatment is not established. New treatment modalities are urgently needed for these patient groups. Rituximab, a monoclonal antibody that is already established in the treatment of adults with mature B-NHL, demonstrated promising results in pediatric patients. The definitive role of rituximab in the treatment of children and adolescents with B-NHL needs to be evaluated in prospective controlled clinical trials. This review provides a comprehensive overview of chemotherapy regimens and the perspectives for children and adolescents with mature B-cell lymphoma and leukemia.